The Role of Sustainable Tourism Development in Promoting Entrepreneurship in Religiously Themed Cities using Social Media.: Peran Pengembangan Pariwisata Berkelanjutan dalam Mendorong Kewirausahaan di Kota-Kota Bertema Agama melalui Media Sosial. - Muhsin Mahdi Rebat Al-kanany (Indonesian Journal of Law and Economics Review, 2026)
General Background: The rapid expansion of digital technologies has transformed global economic structures and reshaped tourism development patterns. Specific Background: Sustainable tourism increasingly depends on the integration of digital platforms, social capital, and community participation to support long-term economic and social outcomes. Knowledge Gap: Despite growing attention, limited studies explicitly examine how digital transformation and social networks jointly contribute to sustainable tourism development. Aims: This study explores the role of digital transformation and social capital in supporting sustainable tourism practices and local economic development. Results: The findings indicate that digital platforms facilitate communication, collaboration, and participation, while social capital strengthens trust and cooperation within communities, contributing to tourism sustainability. Novelty: The study integrates digital transformation and social capital into a unified perspective for understanding sustainable tourism development. Implications: The results suggest that strengthening digital infrastructure and fostering social networks are essential strategies for promoting sustainable tourism and supporting local development. Keywords: Digital Transformation, Social Capital, Sustainable Tourism, Community Participation, Tourism Development Key Findings Highlights Online platforms support community collaboration in tourism activities Trust-based relationships strengthen local participation dynamics Integrated socio-digital factors contribute to long-term development